Panji and Sekartaji on the move - Kieven, Lydia (UI Scholars Hub, 2020)
Since the millenium, the Panji tradition has undergone an increasing process of revitalization and transformation in Java. It shows a broad spectrum of concepts and forms: benefit of a long forgotten cultural heritage, academic approach, popularization, innovation, and its use for strengthening cultural identity. Starting on a grass-roots and community level of artists, intellectuals, and villagers, focusing on the manifestation of values and symbolism, the Panjimania has entered governmental and institutional level throughout recent years, focusing on popularization of art and entertainment in big formats. This boom is also reflected in research and publications on an academic and semi-academic level. The paper discusses the complexity within the state-of-the-art discourse on cultural heritage, for example the risks of instrumentalization, and its major trajectories and potential of this living heritage for the future.